Cross-cultural adaptation of the Intrinsic Motivation Inventory Task Evaluation Questionnaire into Brazilian Portuguese - Nunes, Caio; Darin, Ticianne (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2023: Anais do XXII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2023)
Self-determination theory (SDT) is a psychological theory that has proven relevant in human-computer interaction (HCI) and games studies by providing a greater understanding of what constitutes an engaging experience. SDT conceptualizes intrinsic motivation, described as voluntary behaviors motivated by the person's interest. One approach to evaluate intrinsic motivation in different contexts is using the self-report questionnaire Intrinsic Motivation Inventory (IMI). This paper proposes the cross-cultural adaptation of IMI in its 22-item version, named Task Evaluation Questionnaire, into Brazilian Portuguese. We used the five steps for translation and cross-cultural adaptation of questionnaires proposed by Beaton: Translation, Synthesis, Back-translation, Expert Committee, and Pre-testing. To assure the validity of the translated version, we performed statistical tests, namely, Student's T-test for independent samples, Exploratory Factor Analysis (EFA), and Confirmatory Factor Analysis (CFA). The results showed evidence of the questionnaire's validity and reliability.